Relationship between Profitability and Some of Financial Ratios in Syrian Insurance Companies Using Canonical Correlation (Case Study of Al-Mashreq Al-A’rabi Company) - اديب احمد احمد (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aims to establish any relationship which exists between profitability ratios and some of the financial ratios affecting them (liquidity, subscription and activity turnover ratios) in Syrian insurance companies. The canonical correlation analysis has been applied to the calculated financial ratios based on the financial data of Al-Mashreq Ala’rabi Insurance Company from the reports of the supervisory authority of insurance. The most significant results were that there is a statistical significance between the profitability ratios and the financial ratios (liquidity, subscription and activity turnover ratios). The study also concluded that return on assets is the most closely related ratio to the financial ratios, which can be classified as follows: equity turnover, assets turnover, change in subscription and market share ratios. Furthermore, equity turnover was the most closely related to profitability ratios, followed by assets turnover, change in subscription and market shares respectively. while there is no relationship between profitability ratios and the remaining financial ratios at all.